Pembentukan Karakter Religius Melalui Kegiatan Pembiasaan Amaliyah Sebelum Tidur Di Pondok Pesantren Perkampungan Minang Kabau Al-Falah - Saputra, Indrian; Rehani, Rehani; Zainur, Muhammad (Institut Agama Islam Sumatera Barat, 2024)
Religious character is a conscious, planned, and directed process or method aimed at shaping an individual's attitudes and behaviors positively, adhering to the religious teachings they follow. This research aims to explore the formation of religious character among students (santri) at the Al-Falah Minang Kabau Village Islamic Boarding School, focusing on the practice of pre-sleep